Preparation and Properties of Branched Poly(phosphoric ester) Oligomer and its Influences on Poly(L-lactide) - Bai, Yuqing; Liu, Yingbin; Run, Mingtao (Asian Journal of Chemistry, 2014)
Branched poly(phosphoric ester) (BPPE) oligomer containing intumescent flame retardant were synthesized from spirocyclic pentaerythritol diphosphonate dichloride (SPDPC) and triethanolamine (TEA) and it was blended with poly(L-lactide) (PLLA) to investigate its influences on the thermal and rheological properties of poly(L-Lactide). The results suggest that branched poly(phosphoric ester) oligomer is an intumescent flame retardant whose residual char reaches 47 % at 600 °C and it can partially crystallize into monoclinic crystals. When it was blended with poly(L-lactide), it functions as an intumescent flame retardant, not only widening the degradation temperature range at high temperature but also increasing the residual carbon ratio of poly(L-lactide). Branched poly(phosphoric ester) also serves as a plasticizer for poly(L-lactide) by decreasing the melt viscosity.